The O–P–O bridged Mn2(salen)2 chains showing coexistence of single chain magnet and metamagnet behaviour1. Issue 9 (7th March 2015) - Wang, Ting-Ting; Ren, Min; Bao, Song-Song; Cai, Zhong-Sheng; Liu, Bin; Zheng, Ze-Hua; Xu, Zhong-Li; Zheng, Li-Min
<x xml:space="preserve">Abstract</x> Three chain compounds in which the Mn2(salen)2 dimers are bridged by O–P–O units are reported, two of which display coexistence of SCM behavior and metamagnetism at low temperature.